Alterations of tissue metallothionein and vitellogenin concentrationsin tropical cup oysters (Saccostrea sp.) following short-term (96 h) (2017)
tMetallothioneins and vitellogenins are low molecular weight proteins that have been used widely inenvironmental monitoring as biomarkers of exposure and damage to metals and estrogenic compounds,respectively. In the present study, the responses of metallothionein and vitellogenin tissue concentra-tions were measured following acute (96 h) aqueous exposures to cadmium in Saccostrea sp., a tropicalcup oyster native to the Western Pacific Ocean that has recently established itself in the Caribbean Sea.Adult oysters (1.5–5.0 cm shell length) collected from the municipal marina of Santa Marta, Colombia(Caribbean Sea) and acclimated for 5 days in the laboratory, were exposed to Cd at five concentrations(0, 1, 10, 100 and 1000 g/L) and their tissues (gills, digestive gland and adductor muscle) were analyzedin pools of 5 individuals (3 replicates per concentration). Metallothioneins in digestive glands of oystersexposed to Cd concentrations ≥ 100 g/L showed a significant increase, from 8.0 to 14.8 g MT/mg totalprotein, whereas metallothionein concentrations in gills increased to lesser extent, and no differenceswere observed in adductor muscle. Metallothionein concentrations in digestive gland and gills corre-lated directly with whole soft tissue Cd concentrations (ranging from 2 to 297 g/g dw Cd). Vitellogeninin homogenates of oyster gonad tissue, after 96 h of exposure to 1000 g/L Cd, were significantly lower(0.04 mg P/g gonad) compared to control oysters (0.68 mg P/g gonad), suggestive of an anti-estrogeniceffect of Cd at high concentrations, whereas no significant changes in vitellogenin concentrations wereobserved at intermediate Cd exposure concentrations. This study confirms acute responses of metal-lothionein and vitellogenin concentrations in tissues of Saccostrea sp. exposed to high concentrations ofcadmium (Cd ≥ 100 g/L, 96 h). The present results are first step towards validating the use of these twoproteins as biomarkers of metal exposure in this species.